An overview of high-entropy alloys - Ibrahim, Pshdar Ahmed; Ozkul, Iskender; Canbay, Canan Aksu (Springernature, 2022)
High-entropy alloys (HEAs) are advanced functional and structural materials with advanced marginal properties beyond conventional alloy understanding. It shows the formation of a different and unique microstructure by forming a somewhat complex structure with the understanding of multiple solvers instead of the main solver. The formation of a complex structure causes configurational entropy. The behaviour of added elements in conventional alloys and the conduct of added elements in HEAs, which are almost equimolar added, are based on a different basis. Because of their structure, HEAs are aimed to be an amorphous solid solution. Since it is a new multielement alloy type, existing binary and ternary phase diagrams are not entirely sufficient. HEAs are tried to be defined by some alloying rules. HEAs find applications in different industrial areas thanks to the other physical properties captured. This study reviews the essential criteria in the HEA field, including basic concepts, properties, four core effects, phases, and applications of HEAs. It should be an excellent guideline in HEA's research area.
Keywords: High-entropy alloy (HEA); High-entropy effect; Solid solutions; Core effects; Properties of HEAs; Phase formations